Iliad. Book XXII - Homerus (Cambridge Greek and Latin classics, 2012)
"Book XXII recounts the climax of the Iliad: the fatal encounter between the main defender of Troy and the greatest warrior of the Greeks, which results in the death of Hector and Achilles' revenge for the death of his friend Patroclus; but at the same time adumbrates Achilles' own death and the fall of Troy. The introduction summarises central debates in Homeric scholarship, such as the circumstances of composition and the literary interpretation of an oral poem, and offers synoptic discussions of the structure of the Iliad, the role of the narrator, similes and epithets. There is a separate section on language, which provides a compact list of the most frequent Homeric characteristics. While the introduction is mainly geared at intermediate and advanced students, the commentary is designed for use by both students and professional classicists: it offers up-to-date linguistic guidance, and elucidates narrative techniques, typical elements and central themes"--